Elliptic Problems in with Critical and Singular Discontinuous Nonlinearities. Issue 12 (1st December 2016) - Dhanya, R.; Prashanth, S.; Tiwari, Sweta; Sreenadh, K.
Abstract : Let be a bounded domain in, with smooth boundary, and be real numbers. Define and the characteristic function of a set A by . We consider the following critical problem with singular and discontinuous nonlinearity: We study the existence and the global multiplicity of solutions to the above problem.